A novel approach for finding research areas for new researchers. Issue 3 (3rd July 2019) - Malik, Nouman; Khan, Hikmat Ullah; Faisal, Muhammad Shahzad; Mahmood, Ahsan; Seo, Sanghyun; Bhutta, Muhammad Raheel
ABSTRACT: In academia, choosing a research area is always too important because it determines the future of the researchers. However, in the current scenario, it is not possible for a new researcher to identify the attractive research areas of their interest based on the published papers due to the huge amount of data availability. Therefore, choosing the right research area is of great potential. If the right area for the research is chosen by the researcher, it can help in getting more citations and better research outcome in terms of acceptability of the work. In this paper, our focus was to find attractive research areas for a new scholar. The amount of work done in this research area is very limited therefore, there is very little past work done in this field. In order to identify the attractive research fields for new scientists, we use statistical-based approach to find the new emerging fields and top trends in research as well as comparison of our work with other models used in the same field. The results show that our approach is feasible and we find the attractive research fields effectively from the real-world research paper database in form of DBLP. GRAPHICAL ABSTRACT: